2016
DOI: 10.1002/adma.201602049
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D Metallic Nanostructures on an Arbitrarily Shaped Substrate

Abstract: Constructing conductive/magnetic nanowire arrays with 3D features by electrodeposition remains challenging. An unprecedented fabrication approach that allows to construct metallic (cobalt) nanowires on an arbitrarily shaped surface is reported. The spatial separation of nanowires varies from 70 to 3000 nm and the line width changes from 50 to 250 nm depending on growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Nowadays, plasmonic nanoparticles can be produced in many different ways including chemical synthesis from precursors and direct fabrication on surfaces through either growth in some cases followed by etching, self‐assembly, or top‐down fabrication methods. Nanoparticle preparation through chemical synthesis is extremely versatile in terms of both materials (metals, plasmonic oxides, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, plasmonic nanoparticles can be produced in many different ways including chemical synthesis from precursors and direct fabrication on surfaces through either growth in some cases followed by etching, self‐assembly, or top‐down fabrication methods. Nanoparticle preparation through chemical synthesis is extremely versatile in terms of both materials (metals, plasmonic oxides, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The direct deposition of nanoparticles on surfaces by oblique angle deposition or pulsed laser deposition fails to fully control the arrangement of the grown nano‐objects. Although an impressive control of arrangement of nanowires on any substrate can be achieved through electrodeposition with sine‐shaped oscillatory voltage followed by ion etching, only 1D structures can be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…The commendable tunability for their plasmonic behaviors was easily realized by tailoring nanorod dimensions (i.e., length and diameter), separations between nanorods, and dielectric environments. Currently, from the cost and output point of view, electrochemical deposition method is very popular to fabricate self-organized nanostructures, [20][21][22][23][24] especially for the AAO template-assisted cases. [3,18] For instance, Au nanorods/Al 2 O 3 metamaterial fabricated based on porous anodic aluminum oxide (AAO) template, can exhibit ultrafast optical nonlinearity with a response time of ≈1.13 ps, [18] and the relevant nonlinear gain is believed to be dependent on the delocalized longitudinal (L mode) plasmon resonance.…”
mentioning
confidence: 99%
“…Currently, from the cost and output point of view, electrochemical deposition method is very popular to fabricate self-organized nanostructures, [20][21][22][23][24] especially for the AAO template-assisted cases. Numerous efforts have been made to fabricate nanostructured meta materials, including electron-beam lithography, template-assisted electrochemical deposition, direct laser writing, focused ion-beam (FIB) milling, etc.…”
mentioning
confidence: 99%
“…From an electronic application perspective, a high‐resolution array increases the overall packing density of patterned features, which is critical for miniaturizing semiconductor devices for future applications. Previous studies have shown that the construction of 3D patterned arrays significantly increases the degree of integration, which eventually leads to shorter information access times in microelectronics and spintronics . From a chemical application point of view, the fabrication of carefully designed periodic patterns with a high aspect ratio is desirable for microscale energy‐storage devices with high capacity and rate performance (one application in which these would be required is wearable devices) .…”
Section: Introductionmentioning
confidence: 99%